Driving growth: Breaking down barriers to global prosperity - "Farrell, Diana.(ed.)" (Boston, 2006)
Table Of Contents: The key to growth: breaking down barriers to global prosperity 1 The real new economy 9 Getting IT spending right this time 29 A road map for European economic reform 45 Domestic services: the hidden key to growth 61 Boosting government productivity 83 Beyond cheap labor: lessons for developing economies 107 Don't blame trade for US job losses 125 The hidden dangers of the informal economy 141 Reining in Brazil's informal economy 159 The cost of the gray market in Tur
Keywords: Productivity growth